Optimization of Agricultural Land: A Lesson from Islamic Economics - Ismail, Nurizal; Aisyah, siti (AL- IKTISAB Journal of Islamic Economic Law, 2017)
Human as social being is required to earn the wealth obtained from factors ofproduction to survive in his life. One of the important factors is land, which has beenmostly used in economy such as infrastructure, agriculture and mining. Unfortunately,the use of land tends to give more benefit to capitalist or land-owner than others intodays’ world. It impacts to inequality distribution of income in the society faced in thirdworld country that is mostly in Muslim countries. In Islam, administration of the landhas been concerned in primary sources (Qur’an and Sunnah) and Islamic literatures andpracticed into action in the state such as iqta, ihya al-mawat, zakah, rikaz, muzara’ah,salam, musaqah and other instruments. These instruments are mostly used in agriculturalfield in the Islamic age. Another instrument can contribute to sustainable agriculturaldevelopment is tax land: al-kharaj and al-’usyr. However, the result of this study statesthat to optimize the agricultural land, the state and Islamic banks can contribute togetherto solve the farmers problem such lack of financial support, shortage of water irrigation,lack of training and technology use by integrating appropriate Islamic financing andpolice of land tax that gives benefit and just to the farmers.